DOI: 10.29007/ng9v
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Control of Building Subjected to Harmonic Excitation

Abstract: This paper includes the study of behavior of a single degree of freedom system with viscous dampers subjected to harmonic excitation. In this study one story building is considered. The mathematical model of building subjected to harmonic excitation is obtained and its solution is obtained by state space method. The viscous damper is considered for the building with different percentage of damping. The response of building under resonance and non-resonance condition is obtained and it is observed that it can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similar Clinicopathological concordance of 88.98% was reported by Gupta et al, 19 and 78.38% by Kafle et al 20 Clinico-pathological correlation for granulomatous skin lesion was found to be 41/49 (85%) in present study. The high clinicopathological correlation might be due to open discussion among treating physicians and consultant pathologist whereas concordance between initial clinical impression and histological diagnosis was found in only 63% by Rajbhandari et al, 12 and 61.3% by Gautam et al 2 study by Makwana et al 21 also reported positive concordance rate in 65.7% of cases and they encouraged the use of other advanced diagnostic methods like Polymerase chain reaction (PCR), rapid antigen detection, etc.…”
mentioning
confidence: 99%
“…Similar Clinicopathological concordance of 88.98% was reported by Gupta et al, 19 and 78.38% by Kafle et al 20 Clinico-pathological correlation for granulomatous skin lesion was found to be 41/49 (85%) in present study. The high clinicopathological correlation might be due to open discussion among treating physicians and consultant pathologist whereas concordance between initial clinical impression and histological diagnosis was found in only 63% by Rajbhandari et al, 12 and 61.3% by Gautam et al 2 study by Makwana et al 21 also reported positive concordance rate in 65.7% of cases and they encouraged the use of other advanced diagnostic methods like Polymerase chain reaction (PCR), rapid antigen detection, etc.…”
mentioning
confidence: 99%